Awareness And Consumer Perception To Increase Consumer Purchase Intention In The Platform Lazada E-Commerce - Ervan Kohadi; Ferry Hidayat; Robin (International Journal of Business and Quality Research, 2026)
The purpose of this study is to determine the effect of application user experience, brand awareness, and consumer perception on increasing consumer purchase intention on the Lazada e-commerce platform. The research method used is a quantitative descriptive method. The type of data used in this study is quantitative data, namely data obtained in the form of numbers. The data sources consist of primary and secondary data. Primary data were obtained from questionnaires distributed to respondents, while secondary data were obtained from relevant data and literature related to the issues discussed. The population in this study includes all consumers in Medan City who have made purchases on Lazada, the exact number of which is unknown or considered indeterminate. Therefore, the sampling technique used is the Lemeshow formula, resulting in 96 research samples. Based on the discussion regarding the influence of application user experience, brand awareness, and consumer perception on purchase intention, it can be concluded that these three variables have a significant effect on consumer purchase intention on the Lazada e-commerce platform. Individually, application user experience has a significant influence on purchase intention, as does brand awareness, which is able to increase consumer interest in making purchases, and consumer perception, which also plays an important role in shaping purchase intention. In addition, simultaneously, application user experience, brand awareness, and consumer perception significantly influence consumer purchase intention on the Lazada ecommerce platform.